Exploring alternative possibilities for sublimation measurements over snow and ice surfaces - Huwald, Hendrik; Sigmund, Armin; Gerber, Franziska; Lehning, Michael (2023)
Sublimation of snow is a major depletion mechanism, particularly in dry and windy environments such as high mountains or polar regions. Yet the quantification of the latent heat flux is a difficult task, and both measurements and estimates from models still have large uncertainties. In particular, remote areas in high mountain terrain and on the large polar ice sheets are known to have insufficient spatial coverage through measurements and insufficient capabilities of models to accurately estimate snow sublimation. Additionally, power requirements for eddy covariance (EC) systems are often beyond supply in extreme environments. We present latent heat flux measurements obtained using standard EC instrumentation from several high-alpine and Antarctic field sites and compute corresponding sublimation rates. Where possible, these quantities are compared to sublimation rates derived from measurements of meteorological variables along a vertical profile (bulk approach). This study further explores the suitability of (low-cost) alternative sensors and instrumentation to determine latent heat fluxes over snow and ice-covered surfaces. Specifically, inexpensive fast-response humidity sensors are in the focus of the approach. If successful, this may lead to denser networks of surface stations in the Alps and potentially in polar regions, capable to measure sublimation from snow. A similar approach is tested for fast-frequency air temperature measurements, investigating whether such a methodology is viable in typically stably stratified boundary layers over cold surfaces. At its early stage, this project is largely explorative but may pave the road for interesting and affordable sensing solutions for measuring turbulent heat fluxes in cold, snow and ice-covered environments as standard components on existing traditional automatic weather stations.